The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ac200516c
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Specific Chlorine Isotope Analysis: A Comparison of Gas Chromatography/Isotope Ratio Mass Spectrometry and Gas Chromatography/Quadrupole Mass Spectrometry Methods in an Interlaboratory Study

Abstract: Chlorine isotope analysis of chlorinated hydrocarbons like trichloroethylene (TCE) is of emerging demand because these species are important environmental pollutants. Continuous flow analysis of noncombusted TCE molecules, either by gas chromatography/isotope ratio mass spectrometry (GC/IRMS) or by GC/quadrupole mass spectrometry (GC/qMS), was recently brought forward as innovative analytical solution. Despite early implementations, a benchmark for routine applications has been missing. This study systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 99 publications
(152 citation statements)
references
References 37 publications
4
146
0
2
Order By: Relevance
“…In commercial continuous-flow IRMS, in contrast, CO 2 monitoring gas bypasses the chromatographic system so that errors from chromatography or incomplete combustion are not accounted for, and the amplitudes of sample and reference gas are typically not the same. Such "monitoring gases" are useful to monitor the performance of the mass spectrometer and also to enable crude isotopic calibration of analyte peaks, but they cannot be used to achieve a reliable isotopic calibration on the basis of the "principle of identical e For trichloroethylene (TCE) with GC-quadrupole MS [6] treatment of sample and reference material". The use of a single monitoring gas for calibration also precludes any two-point calibration approach based on two isotopically different reference materials [8,9].…”
Section: Standardization and Referencingmentioning
confidence: 99%
See 2 more Smart Citations
“…In commercial continuous-flow IRMS, in contrast, CO 2 monitoring gas bypasses the chromatographic system so that errors from chromatography or incomplete combustion are not accounted for, and the amplitudes of sample and reference gas are typically not the same. Such "monitoring gases" are useful to monitor the performance of the mass spectrometer and also to enable crude isotopic calibration of analyte peaks, but they cannot be used to achieve a reliable isotopic calibration on the basis of the "principle of identical e For trichloroethylene (TCE) with GC-quadrupole MS [6] treatment of sample and reference material". The use of a single monitoring gas for calibration also precludes any two-point calibration approach based on two isotopically different reference materials [8,9].…”
Section: Standardization and Referencingmentioning
confidence: 99%
“…4 upper panel) [99] or a quadrupole MS [100][101][102]. Instead of species that contain only one chlorine atom (e.g., 37 [101,102], fragment ions [6,99], or a weighted combination of both [100]. The applicability of the isotopologue approach has been theoretically validated [103] and practically investigated [102].…”
Section: Online High Temperature Conversion (Htc) Convertsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration with external standards was performed to receive delta values on the SMOC scale. A recent inter laboratory comparison for different GC-qMS equipment, demonstrated that a lack of calibration of raw GC-qMS chlorine isotope ratios potentially leads to variation of the difference in isotope ratios between two samples by as much as a factor of 1.3 (Bernstein et al, 2011).…”
Section: Chlorine Isotopesmentioning
confidence: 99%
“…Changes in both carbon and chlorine isotope values in the field should be N2‰ so that the degradation is considered significant (Hunkeler et al, 2008;Bernstein et al, 2011).…”
mentioning
confidence: 99%